Management of gun shot injury in a tertiary hospital - A Joshi (Society of Surgeons of Nepal, 2016)
Introduction: Gun shot injury is an uncommon surgical emergency . A timely and multidisciplinary management by surgical team is an essential factor in decreasing mortality and morbidity . This study highlights the multidisciplinary management of gun shot injury.